Taking stock of institutional resource regime research: A meta-analysis. Issue 97 (July 2019) - Lieberherr, Eva; Fischer, Manuel; Tschannen, Amadea
Highlights: The Institutional Research Regime (IRR) literature increasingly focuses on actors and activities. A natural resource focus predominates across time in the IRR literature. We identify three groups of IRR studies: complex, bottom-up and top-down IRR studies. Abstract: This article presents a review of over 100 studies relying on the Institutional Research Regime (IRR) framework. We base the review on a set of 13 elements that cover categories concerning research focus, research design and results. The article first presents the development of IRR studies over time by showing and discussing how different elements of the IRR framework are more or less popular in the literature, and how this popularity develops over time. For example, we have identified a trend in the IRR literature to focus more on actors and activities, while the resource focus predominates across time. Second, the article analyses how different elements of the IRR framework are combined in the existing literature and thus identifies three groups of IRR studies, that is, complex IRR studies, bottom-up IRR studies, and top-down IRR studies.